The Ocular Prosthesis: A Novel Technique Using Digital Photography - Shah, Ronak Mukundkumar (J Indian Prosthodont Soc, 2013)
Loss of an eye can cause a significant psychological and emotional disturbance to any patient. An ocular prosthesis helps to re-establish the physical and mental well-being of the patient. This article describes a novel technique along with a case report for fabricating a predictable, esthetic and well-fitting custom-made ocular prosthesis in an attempt to avoid costly and time consuming procedures that may be required in other methods.